Luminescent ceramics based on polycrystalline calcium fluoroapatite Ca₁₀(P0₄)₆F₂:Eu³⁺ - Babayevskaya, N.V.; Mateychenko, P.V.; Deineka, T.G.; Kolupaeva, Z.I. (Functional Materials, 2008)
The FAP and FAP:Eu³⁺ powders have been prepared using precipitation from aqueous solution. The as-prepared powders were compacted into tablets at 660 MPa and sintered in oxygen atmosphere at 600-1200°C. XRD analysis has shown that within the whole range of sintering temperature, the samples contain crystalline fluorapatite along with a small amount of amorphous phase, which decreases as the sintering temperature rises. The sintering temperature elevation results in extension of the coherent scattering area size (L = 42 to 54 nm). The FAP:Eu³⁺ ceramics density attains 84.67 % at Tsint = 1100°C and decreases above that value. As the temperature increases, the average grain size grows from 5 to 15 μm and the porosity decreases. The photoluminescence efficiency of Eu³⁺ in the FAP structure is maximum for ceramics sintered at 1100°C.